Effect of Dietary Incorporation of Garlic (Allium sativum) and Turmeric (Curcuma longa) Powder and Their Combination on Feed Intake, Haemato-biochemical Parameters and Carcass Traits in Broiler Chicken - Ratika, Khwairakpam; Tiwari, D. P.; Mondal, B.C. (Indian Journal of Animal Nutrition, 2018)
The present study was conducted to discern the effect of dietary incorporation of garlic and turmeric powder as feed additives on feed intake, haemato-biochemical parameters and carcass traits in Top 400 strain of broiler chicken. Day-old broiler chicks (n=120) were procured and randomly distributed into four treatment groups. Each treatment had three replicates with ten chicks in each replicate. The birds of control group (T1) were fed basal diet without any supplementation. In treatment groups T2, T3 and T4, basal diet was supplemented with 3% garlic powder, 0.5% turmeric powder and 1.5% garlic powder plus 0.25% turmeric powder, respectively. The feed intake and growth performance in broiler chicks improved due to feeding of garlic incorporated diets. The haematological parameters were not affected due to dietary incorporation of garlic and turmeric. A significant (P<0.05) reduction in serum cholesterol and triglycerides was recorded in broilers in treatment T2 and T4 as compared to control (T1). Dressing percentage, weight of cut up parts and giblet showed no significant difference among the groups but there was significant (P<0.05) reduction in abdominal fat in broiler chicks due to garlic and turmeric powder supplementation. There was reduction (P<0.05) in cholesterol level of breast muscle in broilers of garlic powder supplemented group T2 (67.12 mg %) as compared to control group T1 (78.39 mg %). Therefore, incorporation of 3% garlic powder in broiler chicken diet improved feed intake and growth performance. Also this treatment resulted in reduced serum cholesterol, triglycerides and improved meat quality by reducing cholesterol level in meat of broiler chicken.